An ambitious development goal: Ending hunger and undernutrition by 2025 - Fan, Shenggen; Polman, Paul (International Food Policy Research Institute, 2014)
Much attention in 2013 was devoted to considering what should follow the Millennium Development Goals, which will come to an end in 2015. This chapter calls for prioritizing the elimination of hunger and undernutrition globally by 2025 and discusses what it will take to achieve that goal.